Simile Expressions in ‘Everything at Once’ Song Lyrics by Lenka - Ria Yuliasari; Rika Virtianti (Pujangga: Jurnal Bahasa dan Sastra, 2022)
In this digital era 4.0, more and more people are realizing the importance of learning foreign languages, especially English. They learn through any source they can access digitally and one of the media used is through music and songs. But actually learning English through songs has its own challenges because song lyrics are often different from spoken language, one of which is the use of language style. This research aims at analyzing simile expressions found in the song lyrics of ‘Everything at Once’ by Lenka. The method used in this research is descriptive qualitative to analyze the types of simile expressions found in the song lyrics. The analysis of the types of simile expressions is carried out using theory of Zhang and Fromilhague. The result of analysis shows that ‘Everything at Once’ song has 38 simile expressions and they all belong to the type of closed and explicit simile. Keywords: simile, song, lyrics.